Analisis Efisiensi Pemasaran Jagung di Provinsi Gorontalo - Ulfira Ashari; Syamsir Syamsir (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2021)
Price fluctuations at the producer and consumer levels determine the performance of the maize market in Gorontalo Province. This will affect the decisions and ability of the corn marketing agencies involved in responding to price changes. The slow response of marketing agencies to changes in maize prices indicates inefficient market conditions in terms of prices. In addition, differences in market power between marketing agencies indicate inefficiencies in marketing maize from an operational perspective. Therefore, this research was conducted with the aim of 1) analyzing market integration and transmission of maize prices between producers and consumers, 2) analyzing the distribution of marketing margins in the maize marketing channels in Gorontalo Province. The research data used is in the form of weekly price data at the producer and consumer levels for 148 weeks, from March 2016 to March 2019 and added data from direct interviews with the marketing actors involved, namely farmers as many as 30 people, while sampling of traders was carried out by snowball sampling technique. Data analysis used the Asymmetric Error Correction Model (AECM), marketing margin and farmer share for each channel. The results showed that the transmission of maize prices at the producer and consumer level is symmetrical in the long run indicating market integration. The smallest marketing margin and the largest farmer share are in Channel III, where marketing is done directly to an exporter. Corn marketing in Gorontalo Province shows price transmission and market integration as well as high farmer share value in each channel, so it can be concluded that marketing is efficient.